Choroidal thickness in Chinese patients with non-arteritic anterior ischemic optic neuropathy. Issue 1 (December 2016) - Jiang, Libin; Chen, Lanlan; Qiu, Xiujuan; Jiang, Ran; Wang, Yaxing; Xu, Liang; Lai, Timothy
Abstract Background Non-arteritic anterior ischemic optic neuropathy (NA-AION) is one of the most common types of ischemic optic neuropathy. Several recent studies suggested that abnormalities of choroidal thickness might be associated with NA-AION. The main objective of this case–control study was to evaluate whether choroidal thickness is an ocular risk factor for the development of NA-AION by evaluating the peripapillary and subfoveal choroidal thicknesses in affected Chinese patients. Methods Forty-four Chinese patients with unilateral NA-AION were recruited and compared with 60 eyes of 60 normal age and refractive-error matched control subjects. Peripapillary and subfoveal choroidal thicknesses were measured by enhanced depth imaging optical coherence tomography. Choroidal thicknesses of eyes with NA-AION and unaffected fellow eyes were compared with normal controls. Choroidal thicknesses of NA-AION eyes with or without optic disc edema were also compared. The correlation between choroidal thickness and retinal nerve fiber layer (RNFL) thickness, logMAR best-corrected visual acuity (BCVA), and the mean deviation (MD) of Humphrey static perimetry in NA-AION eyes were analyzed. Results The peripapillary choroidal thicknesses at the nasal, nasal inferior and temporal inferior segments in NA-AION eyes with optic disc edema were significantly thicker compared with that of normal subjects (P  < 0.05). There was no significant difference in the choroidal thicknesses between the unaffected fellow eyes of NA-AION patients and normal eyes of healthy controls; or between the NA-AION eyes with resolved optic disc edema and normal eyes (allP  > 0.05). No significant correlation between choroidal thickness and RNFL thickness, logMAR BCVA and perimetry MD was found in eyes affected by NA-AION (allP  > 0.05). Conclusions Increase in peripapillary choroid thickness in some segments was found in NA-ION eyes with optic disc edema. However, our findings do not support the hypothesis that choroidal thickness is abnormal in Chinese patients with NA-AION compared with normal subjects with similar age and refractive error status.